A Longitudinal Study of Mental Wellbeing in Students in Aotearoa New Zealand Who Transitioned Into PhD Study - Winter, Taylor; Riordan, Benjamin C.; Hunter, John A.; Tustin, Karen; Gollop, Megan; Taylor, Nicola; Kokaua, Jesse; Poulton, Richie; Scarf, Damian (Frontiers in Psychology, 2021)
Journal editorials, career features, and the popular press commonly talk of a graduate student mental health crisis. To date, studies on graduate student mental health have employed cross-sectional designs, limiting any causal conclusions regarding the relationship between entry into graduate study and mental health. Here, we draw on data from a longitudinal study of undergraduate students in Aotearoa New Zealand, allowing us to compare participants who did, and did not, transition into PhD study following the completion of their undergraduate degree. Using multilevel Bayesian regression, we identified a difference in mental wellbeing between those who entered PhD study and those who did not. This difference, however, was largely due to those not entering PhD study displaying an increase in mental wellbeing. Participants that entered PhD study displayed a small decrease in mental wellbeing, with the posterior distribution of the simple effect heavily overlapping zero. This latter finding was orders of magnitude smaller than one might expect based on previous cross-sectional research and provides an important message; that a marked drop in mental health is not an inevitable consequence of entering graduate study.